The Edinburgh Companion to Sidonius Apollinaris - Press, Edinburgh University (Edinburgh University Press, 2020)
Intro -- Acknowledgements -- Author Biographies -- Note -- Abbreviations for Books, Series, and Reference Works -- Map of Sidonius' Gaul c. 380-c. 480 -- Introduction -- Part I Sidonius' Life, the Characters in his Work, and its Dating -- 1. Sidonius' Biography in Photo Negative -- 2. Sidonius' People -- A Prosopography of Sidonius -- Sidonius' Places: A Geographical Appendix -- 3. Dating the Works of Sidonius -- Part II Sidonius in his Political, Social, and Religious Context -- 4. Sidonius' Political World -- 5. Sidonius' Social World -- 6. Creating Culture and Presenting the Self in Sidonius -- 7. Sidonius and Religion -- Part III Sidonius' Work in its Literary Context -- 8. Sidonius' Intertextuality -- 9. Sidonius' Panegyrics -- 10. Sidonius' Shorter Poems -- 11. Sidonius' Correspondence -- Part IV Sidonius' Language and Style -- 12. Sidonius' Vocabulary, Syntax, and Style -- 13. 'You' and 'I' in Sidonius' Correspondence -- 14. Metrics in Sidonius -- 15. Prose Rhythm in Sidonius -- Part V The Manuscript Tradition and the History of Scholarship -- 16. The Manuscript Tradition of Sidonius -- A Census of the Manuscripts of Sidonius -- 17. Sidonius Scholarship: Fifteenth to Nineteenth Centuries -- 18. Sidonius Scholarship: Twentieth to Twenty-First Centuries -- 19. Translating Sidonius -- Part VI Readers of Sidonius from Antiquity to the Present -- 20. Sidonius' Earliest Reception and Distribution -- 21. Glossing Sidonius in the Middle Ages -- 22. Sidonius in the Middle Ages and the Renaissance -- 23. Sidonius Reception: Sixteenth to Nineteenth Centuries -- 24. Sidonius Reception: Late Nineteenth to Twenty-First Centuries -- Epilogue: Future Approaches to Sidonius -- Bibliography -- Index locorum -- Geographical Index -- Index of Personal Names (Antiquity) -- Index of Personal Names (After Antiquity).